Perlindungan Hukum Bagi Nasabah Pembiayaan Sistem Operasional Grameen Bank di PT. BTPN Syariah Kantor Fungsional Operasional Purbalingga - Saputri, Apik Anitasari Intan (International Conference of Moslem Society, 2016)
In economic development, bank institutions is one of the supporters of the business world where the circulation and financial transactions occur. some financial institutions make women as the main target literacy education, because women responsible for household finances. Grameen Bank is known as rural financial institutions a solution for small communities in developing their business, especially those of women as targets in the development, Grameen bank business that is not only oriented towards profit, but also the social become important in business continuity. Its business objective is to overcome poverty, or other issues (such as education, health, access to technology, and the environment) which threaten people and society is not to maximize profits. Methods used are field research with sociological juridical approach. With the start of the establishment of the poverty alleviation program with many involves women in it, then this must be balanced by a form of protection in full for women to not only become a means of exploitation of business among the owners of capital, but legal protection that women are human beings capable of law and must be protected in the legal transaction activity and every activity. Lack of understanding of the community and also the lack of socialization of banking regulations also triggers the problems that exist in today's society, the lack of responsiveness of banking institutions to its customers, monitoring the use of working capital is very important. How the law is able to protect women as perpetrators of law in the operations of the Grameen Bank, while the whole process of due diligence as members of the business the Grameen Bank are women, they make the process of law through treaties signed in the flow of activities business, agreement collective responsibility that must be borne venture capital disbursed during the period, the pattern together and formed a group that routinely run, business inspection, training, effort and commitment to follow all the rules that promoted by the Grameen bank financial institution operations.